Formation of State Policy of Ukraine towards European Integration - Palagnyuk, Yuliana (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2013)
The peculiarities of the legal and institutional mechanisms of cooperation between Ukraine and the EU in the stage of the formation of the state of Ukraine’s Euro integration policy are analyzed in this paper. The conclusion is made about the nature of cooperation between Ukraine and the EU before the end of the period of formation of Ukraine’s state policy towards European integration.

Przedmiotem niniejszego tekstu jest analiza prawnych i instytucjonalnych mechanizmów współpracy między Ukrainą a Unią Europejską na etapie tworzenia ukraińskiej polityki w kontekście przyszłej integracji państwa z UE.
Tworzenie polityki państwowej na Ukrainie w kontekście integracji europejskiej
Keywords: state policy; Ukraine; European integration; polityka państwowa; Ukraina; integracja europejska